Solidariedade e tutela dos interesses difusos e coletivos: visão interdisciplinar - Coelho, Sérgio Neves (2012)
Solidarity is discussed in this paper under Philosophy, Ethology, Sociobiology, Sociology, Religion and Law concepts, in a bibliographic qualitative research, in order to bring to light that, for the purposes of diffuse and collective rights, the concept to be adopted as the basis for protection is solidarity in an altruistic point of view, in concern about the vulnerability of these interests, whether protected by under sufficient holders (elderly, children and youth) or the difficulty of being defended (environment and public equity). This solidarity do not respect the indivisibility, but when it comes to collaboration, with its meaning that later came to acquire solid, wedded, for cooperation, collaboration, concern for others